Effects of low and medium frequency currents for the treatment of nocturia in women: a randomized clinical trial - Folegatti, Derfel Rodrigo Maciel Alba [UNESP]; Rita, Mell Moreira [UNESP]; Nagami, Danielle Hikaru [UNESP]; Paffetti, Giovanna Saldanha [UNESP]; Gabini, Lívia Grous [UNESP]; Prudencio, Caroline Baldini [UNESP]; Pedroni, Cristiane Rodrigues [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP] (Elsevier, 2025)
Background Nocturia is defined by the International Continence Society (ICS) as the number of mictions during the main sleep period. In a population study carried out in the USA with urology patients with a mean age of 57.3 years, the prevalence of nocturia in women was 41.5%. In recent years, it has been recognized that the causes of nocturia are multifactorial, one of which is bladder overactivity, which in turn can also corroborate the development of Urge Urinary Incontinence (UUI). UUI is present in the lives of thousands of individuals around the world and is a public health problem that affects self-esteem, psychological well-being and often causes these people to isolate themselves from social interaction. Among the treatments recommended for this dysfunction is transcutaneous nerve stimulation (TENS) of the tibial nerve, which has been widely used for the treatment of UUI due to its low cost and minimally invasive nature, in addition to demonstrating significant improvement in clinical conditions. Objectives The aim of the study was to analyze and compare the effects of low- and medium-frequency currents on nocturia reported by participants submitted to treatment. Methods This is a randomized clinical trial was carried out with women aged 18 and over with UUI symptoms, randomly assigned to an intervention with low-frequency current (GTENS-LF) in a symmetrical biphasic pulsed form of 10 Hz and pulse width of 200 ms and another with medium-frequency current (GA-MF) at 4 kHz with bursts of 4 ms and modulation of 100 Hz in continuous mode. Both consisted of 20 sessions of bilateral electrostimulation of the tibial nerve, twice a week. The participants underwent an anamnesis and answered the ICIQ-OAB (International Consultation on Incontinence Questionnaire Overactive Bladder) questionnaire, which has a specific question about nocturia and is reliable in Portuguese. After 20 sessions, the questionnaires were reapplied and the participants were re-evaluated. Results In the first evaluation, the participants allocated to the GTENS-LF group had a score of 2.0 ± 1.8, while the GA-MF group had 2.36 ± 1.89. At the end of the 20 electrostimulation sessions, the GTENS-LF and GA-MF groups' scores were 0.77 ± 073 and 1.06 ± 0.75, respectively. Both groups showed a significant difference compared to the first assessment. Conclusion Analyzing the results, it was possible to conclude that both low-frequency and medium-frequency were able to significantly reduce self-reported nocturia in the study participants, with no difference between the currents. Implications Based on the results of this study, the use of medium- and low-frequency currents becomes a viable alternative for the conservative treatment of patients with urge urinary incontinence.